Identification and functional analysis of ferritin 2 from the Taiga tick Ixodes persulcatus Schulze - Githaka, Naftaly W.; Konnai, S.; Isezaki, M.; Goto, S.; Xavier, M.A.; Fujisawa, S.; Yamada, S.; Okagawa, T.; Maekawa, N.; Logullo, C.; Silva Vaz, I. da; Murata, S.; et al. (Elsevier, 2020)
Ferritin 2 (FER2) is an iron storage protein, which has been shown to be critical for iron homeostasis during blood feeding and reproduction in ticks and is therefore suitable as a component for anti-tick vaccines. In this study, we identified the FER2 of Ixodes persulcatus, a major vector for zoonotic diseases such as Lyme borreliosis and tick-borne relapsing fever in Japan, and investigated its functions. Ixodes persulcatus-derived ferritin 2 (Ip-FER2) showed concentration-dependent iron-binding ability and high amino acid conservation, consistent with FER2s of other tick species. Vaccines containing the recombinant Ip-FER2 elicited a significant reduction of the engorgement weight of adult I. persulcatus. Interestingly, the reduction of engorgement weight was also observed in Ixodes ovatus, a sympatric species of I. persulcatus. In silico analyses of FER2 sequences of I. persulcatus and other ticks showed a greater similarity with I. scapularis and I. ricinus and lesser similarity with Hyalomma anatolicum, Haemaphysalis longicornis, Rhipicephalus microplus, and R. appendiculatus. Moreover, it was observed that the tick FER2 sequences possess conserved regions within the primary structures, and in silico epitope mapping analysis revealed that antigenic regions were also conserved, particularly among Ixodes spp ticks. In conclusion, the data support further protective tick vaccination applications using the Ip-FER2 antigens identified herein.